A Multi-algorithm Approach to the Optimization of Thermal Power Plants Operation - Justino, Gabriela T.; Freitas, Gabriela C.; Batista, Camilla B.; Cotta, Kleyton P.; Deon, Bruno; Loução Jr., Flávio L.; Almeida, Rodrigo J. S. de; Araújo Jr., Carlos A. A. de (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2023: Anais da XII Brazilian Conference on Intelligent Systems, 2023)
A new multi-algorithm approach for the daily optimization of thermal power plants and the Economic Dispatch was tested. For this, the dispatches were clustered in different groups based on their duration and the total power output requested. Genetic Algorithm, Differential Evolution and Simulated Annealing were selected for implementation and were employed according to the distinct characteristics of each dispatch. A monthly improvement of up to 2,45 x 10 5 R$ in the gross profit of the thermal power plant with the use of the optimization tool was estimated.